Results of Railway Privatization in Australia and New Zealand - Williams, Robert; Greig, David; Wallis, Ian (World Bank, Washington, DC, 2014)
This paper has been prepared for the World Bank as one of a series of research papers focusing on rail privatization experience throughout the world. The scope of this paper covers rail privatization experience in Australia and New Zealand, much of which occurred over the ten year period from 1993 to 2003. Overall the rail freight privatization experience in Australia and New Zealand, taken in concert with other market and structural reforms, has been positive, although not uniformly so: In Australia, the largely privatized rail freight industry is markedly stronger today than at any time over the last few decades and is competing aggressively for a greater role in the national transport and logistics market; and In New Zealand, the initial success of privatization with increased rail traffic and increased profits has not been sustained: the government has been obliged to take back the network and to commit significant public funds to address deficiencies in the network assets.